Pathological and molecular characterization of avian malaria in captive Magellanic penguins (Spheniscus magellanicus) in South America - Taunde, Paula Augusto; Bianchi, Matheus Viezzer; Perles, Lívia [UNESP]; da Silva, Fernando Soares; Guim, Tainã Normanton; Stadler, Renan Alves; André, Marcos Rogério [UNESP]; Driemeier, David; Pavarini, Saulo Petinatti (Springer Nature, 2019)
Avian malaria is a mosquito-borne disease that affects multiple avian species and is caused by protozoans of the genus Plasmodium. An avian malaria infection caused by Plasmodium sp. in Magellanic penguins (Spheniscus magellanicus) with high mortality is described in a zoo in Southern Brazil. Clinically, three birds presented signs of inappetence, anorexia, pale mucosa, dyspnea, and opisthotonus, with death in a clinical course of 5–8 h. At the necropsy, all birds exhibited pale mucosa, marked splenomegaly and hepatomegaly, in addition to moderate leptomeningeal blood vessels ingurgitation in the brain. Microscopically, multiple exoerythrocytic meronts were observed in the cytoplasm of endothelial cells in the spleen, liver, heart, lungs, brain, kidneys, and pancreas. The spleen had a multifocal perivascular inflammatory infiltrate of lymphocytes, plasma cells, and macrophages, which also exhibited hemosiderosis and erythrophagocytosis. The liver had a multifocal periportal inflammatory infiltrate of lymphocytes, macrophages, and plasma cells, in addition to marked hemosiderosis in the hepatic sinusoids. Fragments of spleen, liver, brain, skeletal muscle, and lung were tested by the polymerase chain reaction technique for the detection of a fragment of the cytochrome B gene from haemosporidians, which resulted positive for Plasmodium spp. After sequencing, the samples were phylogenetically associated to Plasmodium sp. detected in Turdus albicollis (KU562808) in Brazil and matched to the lineage TURALB01 previously detected in T. albicollis. Avian malaria infections caused by Plasmodium sp. of lineage TURALB01 may occur in S. magellanicus with high mortality, and, thus, it is essential to detect and characterize the agent involved to obtain the differential diagnosis of the condition.
Keywords: Culicidae; Haemosporidian parasites; Morphologic analyses; Phylogenetic analyses; Plasmodium spp